Catálogo Curvas, espartilhos e roupas de baixo: uma história íntima da sedução feminina (séculos XIX e XX) - Vaquinhas, Irene (2021)
This catalogue presents a set of carefully selected items of female underwear dating from the end of the nineteenth century and the beginning of the twentieth century